Guidebook to protein toxins and their use in cell biology - Rappuoli, Rino; Montecucco, C. (Cesare) (Guidebook series (Oxford, England), 1997)
Many bacteria, animals, and plants produce toxins that can prove lethal to other organisms. Toxins are a form of "biological warfare" that helps their producer to survive and so confer an evolutionary advantage. They display an extraordinary range of complexity, from the formic acid provided by ants to bacterial proteins composed of thousands of amino acids. This Guidebook considers the more complex protein and peptide toxins and groups them according to their mode of action.; Topics covered include: membrane-permeabilizing toxins; toxins affecting signal transduction and protein synthesis; cytoskeleton-affecting toxins; toxins affecting the immune and inflammatory response. This class of biomolecules will be of interest to a wide range of researchers in cell biology, ; neuroscience, and toxicology